2020
DOI: 10.1186/s12860-020-00265-2
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 exhibits positive effects on nucleus pulposus cell biology in vivo and in vitro by sponging miR-503

Abstract: Background: Intervertebral disc degeneration (IDD) is characterized by the loss of nucleus pulposus cells (NPCs) and phenotypic abnormalities. Accumulating evidence suggests that long noncoding RNAs (lncRNAs) are involved in the pathogenesis of IDD. In this study, we aimed to investigate the functional effects of lncRNA MALAT1 on NPCs in IDD and the possible mechanism governing these effects. Results: We validated the decreased expression of MALAT1 in the IDD tissues, which was associated with decreased Collag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Firstly, miRNAs could directly bind to mRNA to suppress transcription activity of downstream oncogenes or tumor suppressor genes. In the second place, miRNAs also combine with long non-coding RNAs (lncRNAs) through base pairing, which influences transcription activity of downstream oncogenes or tumor suppressor gene (42). Previous studies have showed that baicalein inhibit the progression of lung cancer (13), hepatocellular carcinoma (40) and osteosarcoma (39, 43) by regulating miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, miRNAs could directly bind to mRNA to suppress transcription activity of downstream oncogenes or tumor suppressor genes. In the second place, miRNAs also combine with long non-coding RNAs (lncRNAs) through base pairing, which influences transcription activity of downstream oncogenes or tumor suppressor gene (42). Previous studies have showed that baicalein inhibit the progression of lung cancer (13), hepatocellular carcinoma (40) and osteosarcoma (39, 43) by regulating miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested that dysregulated lncRNAs exert crucial regulatory functions in multiple processes through acting as ceRNAs to sponge microRNAs (miRNAs) [ 31 ]. MALAT1 was identified to sponge multiple miRNAs, such as miR-124-3p [ 32 ], miR-150-5p [ 33 ], miR-503 [ 34 ], miR-384 [ 35 ], and miR-22 [ 36 ]. To investigate the regulatory mechanism of MALAT1 in mGCs, we selected miRNA interactions with MALAT1 using starBase2.0 software.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue protein was extracted from three samples in each group. NPCs were isolated from nucleus pulposus tissue in three patients with congenital scoliosis or lumbar trauma but not with IDD, because IDD is characterized by the loss of NPCs and phenotypic abnormalities ( Zheng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%